Ovarian Hormones Regulate the Production of Adipocytes From Bone Marrow-Derived Cells - Gavin, Kathleen M.; Sullivan, Timothy M.; Kohrt, Wendy M.; Majka, Susan M.; Klemm, Dwight J. (Frontiers in Endocrinology, 2018)
Sex differences in body fat distribution and menopause-associated shifts in regional adiposity suggest that sex hormones play an important role in regulating the differentiation and distribution of adipocytes, but the underlying mechanisms have not been fully explained. The aim of this study was to determine whether ovarian hormone status influences the production and distribution of adipocytes in adipose tissue arising from bone marrow derived cells. Nine- to ten-week-old ovariectomized (OVX), surgery naïve (WT), and estrogen receptor-α knockout (αERKO) mice, underwent bone marrow transplantation from Luciferase or green fluorescent protein (GFP) expressing donors. A subset of OVX animals had estradiol (E2) added back. Eight-weeks post-transplant, whole body and gonadal fat BM-derived adipocyte production was highest in OVX and αERKO mice, which was attenuated in OVX mice by E2 add-back. All groups demonstrated the highest bone marrow (BM)-derived adipocyte production in the gonadal adipose depot, a visceral fat depot in mice. Taken together, the loss of ovarian hormones increases the production of BM-derived adipocytes. If translatable across species, production of BM-derived adipocytes may be a mechanism by which visceral adiposity increases in estrogen-deficient postmenopausal women.